Find the Product (Refer to the given patterns)
Squaring Binomials
(a + b)² = a² + 2ab + b²
(a - b)² = a² + 2ab + b²
Sum and Difference of Two Terms
(a + b) (a - b) = a² - b²
Foil Method
(x+1)(x+2)
First terms: (x)(x) = x²
Outer Terms: (x)(2) = 2x
Inner Terms: (1)(x) = x
Last Terms: (1)(2) = 2
Combine like terms: 2x + x = 3x
Final Answer: x² + 3 + 2

41. (x + 2)² =
42. (x - 2)² =
43. (x + 1) (x - 1) =
44. (5x + 2) (x - 2) =
45. (3x + 1) (2x + 4) =

Please Maayos na sagot naman :(​


Sagot :

Answer:

41) (x+2)² = (x+2)(x+2)

= x²+2x+2x+4

= x²+4x+4 ans...

42) (x-2)² = (x-2)(x-2)

= x²-2x-2x+4

= x²-4x+4 ans...

43) (x+1)(x-1) = x²-x+x-1

= x²-1 ans...

44) (5x+2)(x-2) = 5x² -10x +2x -4

= 5x² -8x -4 ans..

45) (3x+1)(2x+4) = 6x²+12x+2x+4

= 6x²+14x+4 ans...